(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2024)
This article addresses a forgotten aspect of the history of ideas, namely the fact that one of the most important figures of the twentieth century, Ezra Pound, was influenced by Dantean esotericism and the medieval esoteric doctrine of love proposed in the nineteenth century by Gabriele Rossetti. It aims to show the relations between literature and esotericism, in the wake of a dialogue between the Middle Ages and the twentieth century. The study of this unexplored horizon of research is presented here through the epistolary exchange between Pound and Gabriele Rossetti’s granddaughter, Olivia Rossetti Agresti.